SQL programming style - Celko, Joe (Elsevier/Morgan Kaufmann, 2005)
Joe Celko, maybe one of the most prominent representatives of the database community these days, has written some of the best books about SQL programming in general. This book, however, is different. "SQL Programming Style" doesn't teach you how to become a better SQL developer with SQL puzzles and brainteasers. Rather, it shows you "how to work in logical and declarative terms